(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
This article presents the experience of planning and carrying out the Photographic Walk for Gender Diversity on Wikimedia Commons, a public history and university extension initiative aimed at expanding LGBT+ representation in Wikimedia projects. The event, held in downtown Florianópolis, sought to document and upload images of the LGBT+ community’s memory sites, promoting visibility and digital heritage preservation. Based on this experience, we discuss the challenges and lessons learned in organizing Wikimedia-related events, reflect on the relationship between extension and research, and analyze the photo walk as a practice that connects memory, urban space, and community engagement.